The effect of Enterobius vermicularis infection (oxyuriasis) on eosinophil and IgE levels in allergic rhinitis - Solmaz, Fevzi; Dikici, Oğuzhan; Akduman, Davut; Haksever, Mehmet; Hakyemez, İsmail Necati and Yanılmaz, Muhammed (The European Research Journal, 2018)
Objective: Elevated levels of serum IgE and eosinophilia are the indicators of atopy and intestinal parasitic infections. We evaluated the effect of Enterobius vermicularis infection (enterobiasis) on blood eosinophil count and IgE levels in allergic rhinitis. Methods: A total of 110 patients diagnosed with allergic rhinitis (with symptoms of rhinorrhea, itchy nose and nasal congestion) consisting of 41 (37.27%) males and 69 (62.73%) females were examined. Forty-one (37.27%) patients with enterobiasis were selected as the study group. The remaining 69 (62.73%) patients accepted as the control group. Results: In the study group the mean serum total IgE level and mean serum eosinophil count were 393.10 ± 159.83 IU/mL and 0.56 ± 0.04 103/mL, respectively. In the control group the mean serum total IgE level and mean serum eosinophil count were 236.91 ± 63.55 IU/mL and 0.37 ± 0.12 103/mL, respectively. The difference between the two groups was statistically significant for serum total IgE levels (p < 0.05) but not for serum eosinophil count (p > 0.05). The correlation coefficients between serum total IgE level and eosinophil count were statistically insignificant (p > 0.05). Conclusions: More comprehensive and long-term placebo-controlled studies should be performed in order to find the answer to the question of whether helminth infections play a role in allergic disease.